2006
DOI: 10.1139/x06-137
|View full text |Cite
|
Sign up to set email alerts
|

Nonconstituent species in soil seed banks as indicators of anthropogenic disturbance in forest fragments

Abstract: Forest fragmentation is prevalent in regions with high human population density, but also with high biological diversity, such as southwestern China. Predicting potential changes in species composition in native forest ecosystems resulting from forest fragmentation is an important approach in assessing forest ecosystems and sustainable management of forests. The term nonconstituent species is proposed for plant species that occur in a natural landscape but are not native to it. We hypothesized that fragmentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 33 publications
3
20
0
1
Order By: Relevance
“…The significant changes of plant composition in understory vegetation at forest edges could occur over a few years to decades after edge creation (Matlack, 1994;Meiners and Pickett, 1999;Harper and Macdonald, 2002), which might be attributed to the long-term accumulation of external seeds at forest edges. We have found that the invasion of non-forest species in understory vegetation lags behind that in soil seed banks in the forest interior (>200 m into the forest from the edge) (Lin et al, 2006). However, for the forest edge, we still do not know the contrasting response of non-forest species in soil seed banks and understory vegetation.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…The significant changes of plant composition in understory vegetation at forest edges could occur over a few years to decades after edge creation (Matlack, 1994;Meiners and Pickett, 1999;Harper and Macdonald, 2002), which might be attributed to the long-term accumulation of external seeds at forest edges. We have found that the invasion of non-forest species in understory vegetation lags behind that in soil seed banks in the forest interior (>200 m into the forest from the edge) (Lin et al, 2006). However, for the forest edge, we still do not know the contrasting response of non-forest species in soil seed banks and understory vegetation.…”
Section: Introductionmentioning
confidence: 84%
“…Non-forest species are species growing in habitats different from closed forests or their successional communities and usually include native and non-native weeds and plants that have escaped from cultivation (Lin et al, 2006). In this study, we used this categorization to explore the general pattern of plant species responses to the forest edge.…”
Section: Introductionmentioning
confidence: 99%
“…are an important component of the soil seed banks of Asian tropical and subtropical forests (Chandrashekara & Ramakrishanan, 1993;Lin et al, 2006;Metcalfe & Turner, 1998), we predict that seeds of M. indica will be present in the soils that we sampled, but at much higher densities in the soils of abandoned cardamom plantations than adjacent natural forests.…”
Section: Introductionmentioning
confidence: 78%
“…The greater abundance of the Elettaria presumably reflects increasing propagule pressure arising from reproduction of the residual cardamom plants, (Dalling & Denslow, 1998;Lin et al, 2006;Tang et al, 2006). Taken together, the higher abundance of herbs, light-demanding trees and non-native species in the seed banks of CP than NF explains their separation into distinct clusters in ordination space, and suggests that they represent distinct floristic communities.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation